Assortative mating, sexual size dimorphism and sex determination in a seabird with plumage polymorphism. Issue 1 (2nd January 2019) - Leal, Gustavo R.; Nunes, Guilherme T.; Oliveira, Gabriela; Bugoni, Leandro
ABSTRACT: Intraspecific plumage polymorphism in seabirds is often attributed to advantages in foraging activities and escape from predators, but its role in sexual selection is not well understood. The Trindade petrel ( Pterodroma arminjoniana ) presents morphs varying from pale to whole dark, with no apparent sexual size dimorphism (SSD). We tested assortative mating in Trindade petrels based on plumage colours and body size. In addition, genders of Trindade petrels were identified molecularly aiming to test SSD based on morphometrics, which was also used to generate a discriminant function for sex assignment. Within-pair consistency in plumage colour (i.e. birds paired with mates of the same morph) was detected in 9 out of 10 pairs, but not in morphometric traits. Minimum bill depth and bill depth at unguis were traits significantly larger in males. The best model was adjusted with Bill depth at unguis, wing chord and body mass, with global discriminatory power of 78.4%. Our results suggest that plumage colours may be sexually selected in Trindade petrels, which brings evolutionary implications on the persistence of plumage polymorphism. Discriminatory power of the best discriminant function was similar to those found in other Procellariiformes and also among datasets obtained by distinct researchers, demonstrating its robustness.